Penguatan Pemahaman Keagamaan Siswa Sekolah Dasar melalui Pelatihan Fiqh Ubudiyah - Hadi Ismanto; Ravita Rahmatika; Abqoriyah Yumna (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2025)
Strengthening religious understanding from an early age is an important need in the formation of the religious character of elementary school students. This religious service activity has an impact on improving students' religious understanding, skills and attitudes. This activity was carried out at the Baitul Muttaqin Mosque with a target of 35 students in grades 5 and 6 of the Bulurejo 1 Public Elementary School UPT. The program focused on training in Islamic jurisprudence in the form of procedures for ablution and obligatory prayers according to Islamic law. The method used was Participatory Action Research (PAR) through interactive lectures, demonstrations, direct practice, and evaluation. The results of the activity showed significant improvements in three aspects: knowledge, ± 90% of students were able to state the pillars and conditions for valid ablution and prayer; skills, ± 85% of students were able to practice ablution and prayer movements correctly; and attitudes, more than 80% of students demonstrated discipline, maintained cleanliness, and sincerity in worship.